СЕРДЕЧНО-СОСУДИСТАЯ СИСТЕМА И ХРОНИЧЕСКАЯ БОЛЕЗНЬ ПОЧЕК - Х. Х. Шугушев; Ф. М. Багова; М. Ж. Аттаева (SINAPS LLC, 2012)
The chronic disease of kidneys represents a serious problem of the world health service. Last years there has been an important increase of patients with chronic kidney disease, literature revealed new information about character lesions of the cardiovascular system at patients with chronic kidney disease. This article shows that the combination of chronic kidney disease with cardiovascular pathology makes worse the prognosis of life. In this context, a special role plays an exploring the possibilities of timely correction of the treatment of these diseases.